El derecho a la identidad sobre las nuevas técnicas de reproducción humana asistida, Guaranda 2022. - Cuichan Curicho, Jhon Kevin (2024)
The work entitled: "The right to identity on the new assisted human reproduction techniques, Guaranda 2022". It addressed the right to identity from the perspective of children's rights, because it is constituted immediately after birth, through the filiation that gives the child, all the rights arising from family relationships. It is in this context that the new techniques of assisted human reproduction were also addressed, as a new element against which the Law has not been able to update, especially in Ecuador where there is no regulation establishing the way in which the information related to procreation must be treated. In other words, the human being procreated by means of one of these techniques cannot have access to the information related to his progenitors, because there is no database to be filled in by the health centers that perform these procedures, therefore, the procreated person cannot know his own origin, which is one of the elements of the right to identity. The general objective of this paper was to address the new assisted human reproduction techniques with a view to guaranteeing the right to identity. The research method used corresponded to the qualitative approach typical of the social sciences, such as legal analysis and interpretative methods (textual, systematic, descriptive, historical). However, it was also necessary to use the quantitative approach to confirm through experts the statements expressed throughout the research process. Although this study was deeply descriptive in nature, it was not experimental in the sense that the variables did not need to be manipulated. Interpretative techniques were used to process information contained in documents such as laws, doctrines, reports and jurisprudence. A document analysis guide was used for document analysis. Therefore, this study is purely theoretical in nature and focused only on confirming what was proposed. Surveys were also XX conducted with experts in the field and the survey guide was used. Finally, the study reached its main conclusions and recommendations, applying a comprehensive process. Key words: knowing one's own origin, biological truth, right to truth, static dimension.